Early years spending update: The impact of inflation - Elaine Drayton; Christine Farquharson (Institute for Fiscal Studies (IFS), 2022)
With the COVID-19 lockdowns and the ongoing cost-of-living crisis, the importance of the early years system for children and their parents has been made particularly obvious over the last few years. In this report, we analyse how public spending on early childhood education and care has changed over the last two decades. Overall spending on the early years in England has grown from around 1.5 billion in 2001-02 to more than 5.3 billion last year (all figures in today's prices). But within this growing envelope, the relative amount of spending on the different childcare programmes has changed dramatically. The 'free entitlement' to funded childcare hours - for all 3- and 4-year-olds and some 2-year-olds - has seen its budget grow substantially, while spending on childcare subsidies through the working-age benefit system has been cut.
Keywords: 330; Education and skills; Education spending; Childcare and early years; Inflation; Government spending; Education; Early childhood development; COVID-19; Tax; Trends; Universal credit; Working age benefits